ANALISIS FAKTOR DETERMINAN PENGAMBILAN KEPUTUSAN INVESTASI DI PASAR KRIPTO - Wahyudi, Andi; Mukhlis, Mukhlis; Nova, Nova; Musrizal, Musrizal (Ekonomika Journal, 2024)
Investors often make irrational investment decisions. Decisions are often based on judgments that are far from rational assumptions. This research aims to examine the influence of experience regret, risk tolerance, illusion of control and financial literacy on investment decisions in the crypto market. Data was collected using an online media-based questionnaire instrument via Google Form involving 112 investor respondents who actively invest in cryptocurrencies. The data was processed and analyzed using the E-Views 10 software application. The types of data in this research are primary and secondary data using quantitative research methods and multiple linear regression models. The results of this research show that experience regret, risk tolerance and illusion of control do not influence investment decisions in the crypto market. Meanwhile, financial literacy influences investment decisions in the crypto market but at a significance level of 10 percent. It is very necessary to have clear regulations in the crypto market in an effort to provide protection to investors. Remember, the definition of crypto currency has different views.